Farmers’ preferences for climate-resilient potatoes in Kenya - Kimathi, Sally; Ruto, Eric (CGIAR, 2024)
Potatoes play a vital role in Kenya’s agricultural sector, contributing significantly to food security and household incomes. As one of the country’s staple crops, potatoes are particularly important for smallholder farmers, who depend on them for both subsistence and commercial purposes. However, the challenges posed by climate change, including emerging pests, diseases, and water scarcity, have jeopardized potato production (Challinor et al. 2016; International Potato Center 2017). These challenges are now especially acute in regions like Meru County, a leading potato-producing area with diverse agro-ecological zones.